The role of extracellular vesicles in the physiological and pathological regulation of the blood–brain barrier. Issue 9 (23rd July 2021) - Busatto, Sara; Morad, Golnaz; Guo, Peng; Moses, Marsha A.
Abstract: Extracellular vesicles (EVs) are a subclass of biological nanoparticles secreted by most cell types. Once secreted, EVs can travel long distances to deliver their content to target cells thereby playing a key role in cell‐to‐cell communication and supporting both physiological and pathological processes. In recent years, the functional versatility of EVs has come to be more widely appreciated. Their heterogeneous structure encloses solubilized bioactive cargoes including proteins and nucleic acids. EVs mirror the secreting cell in composition therefore representing a novel source of diagnostic and prognostic biomarkers. Moreover, due to their unique structure, EVs constitute a promising class of biocompatible nanovehicles for drug delivery as well. Importantly, and of burgeoning interest, is the fact that EVs have the intrinsic ability to breach biological barriers including the complex blood–brain barrier (BBB), whose restrictive nature represents a significant therapeutic challenge. EVs have been shown to contribute to the progression of a variety of brain diseases including metastatic brain cancer, neurodegenerative diseases, and acute pathologies including infections and ischemia. In this review, the role of EVs in the maintenance and regulation of the BBB under normal physiological and pathologic conditions are discussed. Applications of EVs as therapeutic and diagnostic tools in the treatment of diseases that affect the central nervous system are presented as are limitations hindering their broad translation and potential solutions to resolve them.